KEBIJAKAN FORMULASI TERKAIT KONSEPSI RECHTERLIJKE PARDON (PERMAAFAN HAKIM) DALAM PEMBAHARUAN HUKUM PIDANA DI INDONESIA - Aska Yosuki; Dian Andriawan Daeng Tawang (Fakultas Hukum Universitas Tarumanagara, 2018)
The effort of reforming criminal law in Indonesia, particularly the regulations, has been conducted since 1963, proven by the formulation of Penal Code Bill, however, until now, the Penal Code Bill has not been passed. One of the ideas in the Penal Code Bill is the concept of Rechterlijk Pardon. This concept is crystallized because of the current criminal law is too rigid and lack of humanity sense in applying to minor cases.This research aims to describe the concept of Rechterlijk Pardon and the basis of the concept in the Penal Code Bill in Indonesia. The result of the research is that the concept of Rechterlijk Pardon desires that in imposing criminal sanctions, the judges shall not only consider the criminal act and criminal responsibility, but also the objectives and guidelines of imposing criminal sanctions. The objectives and guidelines have been explicitly regulated in Article 55 and 56 of Penal Code Bill. Whenever the judges believe that imposing criminal sanctions is not consistent with its purpose and guidelines, the judges is possible to give pardon. The essence of this concept is that when the prosecutor successfully proves its indictment and the perpetrator was given pardon by the judges, there will be no criminal sanctions that will be imposed on the perpetrator. The form of the verdict is a guilty verdict without punishment. The basis of this concept are the philosophical, sociological, juridical, and teoritical basis.